Fuel characterization and thermogravimetric analysis of melon (Citrullus сolocynthis L.) seed husk - Nyakuma, Bemgba; Oladokun, Olagoke; Dodo, Yakubu; Wong, Syie; Uthman, Habibu; Halim, Muhamad (Publishing House of Lviv Polytechnic National University, 2016)
The thermochemical fuel properties of melon seed husk (MSH) were characterized to examine its solid biofuel (SBF) potential for future bioenergy utilization. MSH is a cheap, abundant and renewable source of lignocellulosic waste generated from the extraction of vegetable oil from melon seeds. Thermochemical characterization was examined by proximate, ultimate, and thermogravimetric (TG-DTG) analyses, as well as Fourier transform infra-red (FT-IR) spectroscopy. The results showed that MSH exhibits significant volatile matter, fixed carbon, carbon and low nitrogen, sulphur and ash content with a heating value (HHV) of 19.02 MJ/kg. FTIR analysis indicated functional groups for aliphatic, ester, ketone, alcohol, and aromatic compounds. Thermal decomposition of MSH occurred in three stages: drying (303–448 K), devolatization (448–673 K) and char degradation (673–1073 K). Визначено термохімічні паливні властивості лушпиння насіння колоцинту (ЛНК) з метою його потенційного використання як твердого біопалива. Показано, що ЛНК є дешевим, доступним і відновлювальним джерелом лігноцелюлозних відходів, які одержують при екстракції олії з насіння дині. Проведено дослідження з використанням технічного, елементарного і термогравіметричного (TГ-ДТГ) аналізів, а також Фур’є-спектроскопії. Встановлено, що ЛНК містить значну кількість летких речовин і зв’язаного вуглецю, а також невелику кількість азоту, сірки і золи з теплотворною здатністю понад 19,02 МДж/кг. За допомогою Фур’є-спектроскопії встановлена присутність аліфатичних, естерних, кетонних, спиртових і ароматичних функційних груп. Показано, що термічний розклад ЛНК відбувається в три етапи: висушування (303–448 К), оброблення (448–673 К) і розклад залишку (673–1073 К).
Паливні характеристики та термогравіметричний аналіз лушпиння насіння колоцинту (Citrillus сolocynthis L.)
Keywords: melon; seed husk; biofuel; characterization; thermogravimetry; spectroscopy; колоцинт; лушпиння насіння; біопаливо; характеристика; термогравіметрія; спектроскопія